Neutrophil to lymphocyte (NTL) ratio and its prognostic significance in patients with diabetic foot syndrome (DFS) - Sarwat Bibi; Sara Jabbar; Zeeshan Ali; Khurram Saqib; Humaira Ahmad; Muhammad Saleem (Journal of University Medical & Dental College, 2022)
BACKGROUND & OBJECTIVE: Neutrophil to lymphocyte ratio has an important role to predict the outcome of diabetic foot syndrome. The aim is to evaluate NTL ratio as a prognostic factor in diabetic foot syndrome and its importance in diabetic wounds.METHODOLOGY: Descriptive cross-sectional study was to evaluate NTL ratio for prognosis of DFS. All cases were assessed for smoking, body mass index, presence of wound, glycated hemoglobin level, peripheral limb ischemia and infection. Patients were examined for a period of 12 months to assess wound if it resulted in minor amputation (below the level of ankle), major amputations (below/above knee amputation), chronic wound or completely healed wound. Chi-Square test was applied for categorical data.RESULTS: Total 100 patients were included and 61% were smokers. Average BMI was 31.7 and 34.5 in males and  females. Complete wound healing found in 18% cases after debridement and chronic wounds in 15% patients. Subjects had to undergo major (above ankle) 16% and minor (below ankle) 51% amputations. Mean NTL count was 3.5 in fully healed wounds, 4.3 in chronic wounds, 6.9 in major amputations, and 5.2 in minor amputations. As the p-value indicates, there is a significant relationship between healed wounds, minor amputations, Chronic wounds and major amputations and the NTL ratio.CONCLUSION: Results revealed NTL ratio has independent prognosis in DFS for anticipating wound upshot. NTL ratio has a significant link with healed wounds, minor amputations, and major amputations, as indicated by p-value.